Mental health during the Covid-19 quarantine in five countries (2021)
Introduction. As part of the holistic concept of health, mental health can be focused on prevention of contagion and coping with the disease and its consequences in the context of the current COVID-19 pandemic. The present study describes, compares, and analyzes the association of the impact of the event, perceived stress, coping strategies, emotional regula-tion, and sociodemographic characteristics during the quarantine in various countries. Material and methods. This research is a multicentric and epidemiological study with a convenience online snowball sampling of the general population and university students. Results. 1.179 participants from Colombia, Brazil, Mexico, Italy, and Spain responded to the survey. Most of them included students and workers, with a high educational level and living with family during the quarantine. There are significant differences in the medians of all variables among countries and sociodemographic characteristics. The variables positively and significantly associated with the impact of the event during quarantine included the perceived stress, the coping strategies of alcohol/drug use, planning and active coping, focus on emotions and vent, the emotional regulation strategy expressive suppression, and living in Italy. Conclusions. These results have contributed to the understanding of mental, emotional, and behavioral response to quarantine, as well as underline the urgency of monitoring men-tal health among the vulnerable groups, in order to design specific prevention and interven-tion programs.